Protective factors as uni- or bipolar factors and their incremental validity and accuracy in predicting general recidivism. (March 2022) - Eisenberg, M.J.; van Horn, J.E.; van der Put, C.E.; Stams, G.J.J.M.; Hendriks, Jan
Abstract: This study examined whether protective factors are unique or the opposite of risk factors and whether they have incremental validity in the prediction of general recidivism. Using a sample of 3306 Dutch forensic outpatients, this study was the first large-sample study ever performed on this topic. Results from exploratory factor analyses demonstrated a relatively stable factor structure of 14 factors, consisting of 32 of the initially included 68 risk factors and 11 of the initially included 17 protective items. The protective factors were found to be either bipolar (i.e., mirror images of risk factors) or responsivity characteristics (i.e., motivation for treatment, cognitive disability). Incremental validity for the recidivism prediction was found in one factor with internal protective items (e.g., empathy, financial management, life goals). This factor decreased the recidivism risk by 6%. However, weak predictive accuracy was found for this factor. Implications for clinical forensic practice are discussed with special focus on the risk-need-responsivity model.